Implementasi Kebijakan Pendidikan Inklusif Jenjang Sekolah Dasar - Irmawati, Irmawati; Rahmawati, Rita; Rusliandy, Rusliandy (Laboratorium Administrasi Publik FISIP Universitas Andalas, 2024)
Inclusive education in Bogor City is the main focus of achieving equitable and quality education for all, including children with special needs (ABK). Although there are currently inclusion regulations, their implementation is still faced with challenges. The purpose of this study is to describe how inclusion policies are implemented in primary schools. This research uses qualitative methodology with field studies at SDN Perwira, SDN Batutulis 2, and SDN Pakuan. Research informants totaled 14 people who were determined using purposive sampling techniques. Data was collected through observations, documentation, and interviews. Data analysis takes place according to the stages of Miles and Huberman, which include data collection, data reduction, data presentation, and conclusion-making. Research findings show that implementing inclusion policies faces challenges such as uneven distribution of students with special needs and limited resources. Nevertheless, there is commitment and support from local government implementers and regulations. There needs to be improved coordination and better policy structuring to improve performance at the school level.